Can Obviously Intoxicated Patrons Still Easily Buy Alcohol at On‐Premise Establishments?. (18th February 2016) - Toomey, Traci L.; Lenk, Kathleen M.; Nederhoff, Dawn M.; Nelson, Toben F.; Ecklund, Alexandra M.; Horvath, Keith J.; Erickson, Darin J.
Abstract : Background: Excessive alcohol consumption at licensed alcohol establishments (i.e., bars and restaurants) has been directly linked to alcohol‐related problems such as traffic crashes and violence. Historically, alcohol establishments have had a high likelihood of selling alcohol to obviously intoxicated patrons (also referred to as "overservice") despite laws prohibiting these sales. Given the risks associated with overservice and the need for up‐to‐date data, it is critical that we monitor the likelihood of sales to obviously intoxicated patrons. Methods: To assess the current likelihood of a licensed alcohol establishment selling alcohol to an obviously intoxicated patron, we conducted pseudo‐intoxicated purchase attempts (i.e., actors attempt to purchase alcohol while acting out obvious signs of intoxication) at 340 establishments in 1 Midwestern metropolitan area. We also measured characteristics of the establishments, the pseudo‐intoxicated patrons, the servers, the managers, and the neighborhoods to assess whether these characteristics were associated with likelihood of sales of obviously intoxicated patrons. We assessed these associations with bivariate and multivariate regression models. Results: Pseudo‐intoxicated buyers were able to purchase alcohol at 82% of the establishments. In the fully adjusted multivariate regression model, only 1 of the characteristics we assessed was significantly associated with likelihood of selling to intoxicated patrons—establishments owned by a corporate entity had 3.6 greater odds of selling alcohol to a pseudo‐intoxicated buyer compared to independently owned establishments. Conclusions: Given the risks associated with overservice of alcohol, more resources should be devoted first to identify effective interventions for decreasing overservice of alcohol and then to educate practitioners who are working in their communities to address this public health problem.